Metabolism and Biodegradation of β-Glucan in vivo - Zheng, Ziming; Tang, Wenqi; Lu, Weipeng; Mu, Xu; Liu, Yuxuan; Pan, Xianglin; Wang, Kaiping; Zhang, Yu (Frontiers in Veterinary Science, 2022)
β-Glucans widely exist in plants and edible fungi, and their diverse bioactivities and good physicochemical properties have been widely reported. In addition, β-glucan intravenous injections (such as lentinan and schizophyllan) have been clinically used as immunomodulators and antitumor polysaccharides. However, the pharmacokinetic studies of β-glucans only stay on the level of plasma concentration and biodistribution in vivo, and little is known about their metabolism and degradation in vivo, which severely limits the further application of β-glucans in the field of medicine and biomaterials. The aim of this paper is to explore the metabolism and degradation process of lentinan (as a representative of β-glucans) in vivo by labeling with water-soluble fluorescein 5-([4,6-Dichlorotriazin-2-yl]amino)fluorescein (DTAF). Fluorescently labeled lentinan (FLNT) was intravenously administered to rats at a single dose of 8 mg/kg. The degradation of LNT in blood, liver, kidney and urine was evaluated by gel permeation chromatography. Our results showed that although LNT could be degraded in blood, liver, kidney and urine, there were still some prototypes until excreted in urine due to the incomplete degradation of LNT in each step. To the best of our knowledge, this is the first report to comprehensively study LNT metabolic degradation in rats. These results provide an important reference for further exploration and application of LNT and other β-glucans.